Microfinance Mission Drift? - Roy Mersland; R. Øystein Strøm (World Development, 2010)
Claims have been made that microfinance institutions (MFIs) experience mission drift as they increasingly cater to customers who are better off than their original customers. We investigate mission drift using average loan size as a main proxy and the MFI's lending methodology, main market, and gender bias as further mission drift measures. We employ a large data set of rated, multi-country MFIs spanning 11 years, and perform panel data estimations with instruments. We find that the average loan size has not increased in the industry as a whole, nor is there a tendency towards more individual loans or a higher proportion of lending to urban costumers. Regressions show that an increase in average profit and average cost tends to increase average loan and the other drift measures. More focus should be given to cost efficiency in the MFI.
Keywords: 650